IgE-mediated hypersensitivity after ibuprofen administration - Bluth, MH (2012)
Although many immunoglobulin-related drug sensitivities have been described, there is a paucity of reports regarding IgE-related drug sensitivities. Here we describe a case of a patient who demonstrated IgE-mediated sensitivity to ibuprofen.